Geographical analysis of rainfall variability and its impact on climatic water balance in Penjwen district - احمد, پ.د. سۆران حمه امین احمد; محمد, چنوور امین محمد (Sulaimani Journal for Humanities, 2025)
the aim of this research is to conduct a geographical analysis of rainfall fluctuations, demonstrating the variability and deviation in annual rainfall amounts. and their impacts on excess water levels and the climatic water balance in Penjwen district, Penjwen is one of the border districts in Slemani Governorate, with a total area of 1138 km², To assess the impact of rainfall fluctuation on the district, data recorded by the Penjwen Weather Department(2003-2024) were utilized, The data were analyzed using several statistical methods and mathematical equations to determine the impact of rainfall variability on water level changes within the district, The Thornthwaite and Ivanov equations were specifically employed to calculate the water balance and excess water, Additionally factors influencing rainfall amounts are discussed. The research concluded that rainfall fluctuation is an inherent characteristic of the region, exhibiting an average annual variability (or coefficient of variation) of 29.7%, peaking at 428.6% in September, this rainfall irregularity significantly impacted the water balance and excess water in the district, leading to the classification of years such as "wet" (e.g., 2018-2019) and "dry" (e.g., 2007-2008), The highest water surplus was observed in December, January, February, and March. The estimated annual water surplus for the district is 1047049956 m³. A strong positive correlation (Pearson's coefficient) was found between rainfall and the climatic water balance.
Keywords: Climate; Rainfall Fluctuations; Excess Water; Climatic Water Balance; rainfall; Pearson Correlation